A cross-tissue transcriptome-wide association study identified susceptibility genes for age-related macular degeneration - Hongfan Yang; Haofei Huang; Kunlin Pu (Scientific Reports)
Abstract Age-related macular degeneration (AMD) is a complex multifactorial disease with a significant genetic component. Despite extensive research efforts, the underlying molecular mechanisms remain elusive, necessitating innovative approaches to identify specific genes involved in the pathogenesis of AMD and to elucidate their functional mechanisms. A transcriptome-wide association study (TWAS) was conducted by integrating eQTL data from 49 tissues of the Genotype-Tissue Expression Project (GTEx) v8 and AMD data from FinnGen R10. The Unified Test for Molecular Signatures (UTMOST) and Functional Summary-based Imputation (FUSION) were used to evaluate gene associations with AMD across tissues and within individual tissues, respectively. Multi-marker Analysis of Genomic Annotation (MAGMA) was employed to validate results and identify reliable susceptibility genes, followed by summary data-based Mendelian randomization (SMR) and colocalization analyses to explore causal associations. The cross-tissue and single-tissue TWAS analyses identified 12 reliable AMD-associated genes. MAGMA analysis confirmed 6 of these as reliable susceptibility genes. SMR analysis provided further validation of these genes, although colocalization results were not significant. This study identified six susceptibility genes associated with the risk of AMD through a cross-tissue TWAS, providing new insights into the potential systemic regulatory mechanisms underlying AMD.